POSSIBILITY OF CULTIVATION OF OILSEED CULTURES IN RADIOACTIVE POLLUTED TERRITORIES - Teteruk, Olena; Feshchenko, V. (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
As a result of the Chernobyl accident, the most severe scenario for the consequences for agriculture in Ukraine was implemented: more than five million hectares of land on which products are produced and about three million people are contaminated. The determining factor in the intensification of agricultural production in the area of radioactive contamination is the maximum use of opportunities of those crops that play a significant role in the production of food, feed, consumer goods and do not accumulate radionuclides in finished products. The research was conducted in stationary field experiments, located near the village of Khrystynivka (Narodytsky district Zhytomyr region) on turf-podzolic sandy soils. Agrotechnical cultivation is generally accepted for the Polissya area. The accounting area of each site on which the particular version of the experiment is conducted is 10,15 m2, the repetition of the four-time. Breakdown of the experimental plot, field work on the experimental site, fertilization, soil cultivation, seeding, plant care and trial, crop accounting was performed according to generally accepted methods. The article presents the results of a study on the specific activity of cesium-137 in green mass and seed oilseeds, for example, white mustard and coleseed. These varieties are suitable for cultivation in radioactive contaminated areas, as evidenced by the yield data and the use of green masses of crops for feed and seeds for oil.